Differential characteristics and treatment of psoriasis patients by economic status in South Korea: An analysis of the National Health Insurance Database. Issue 46 (13th November 2020) - Ha, Dongmun; Ryu, Jinchol; Chun, Yoonsoo; Song, Inmyung; Shin, Ju-Young
Abstract : Abstract: Despite the enormous burden on patients with severe psoriasis, their utilization of medical care is not well understood in Korea. To compare the characteristics and treatment patterns of psoriasis patients by economic status as well as to examine the factors influencing systemic treatments of psoriasis. We conducted a descriptive cross-sectional study using National Health Insurance sample cohort data in 2015. Psoriasis patients were classified as either the "topical treatment only" or the "systemic treatment" group based on the types of treatment. Patients' economic status was defined by the deciles of health insurance premium, which was determined based on income and assets. Multivariate logistic regression analysis was performed to examine the factors influencing systemic treatments of psoriasis. We identified 6041 psoriasis patients; 39.5% were in the bottom 5 deciles of health insurance premium and 60.5% were in the top 5 deciles. Only 1.9% of the low economic status group and 4.0% of the high economic status group were treated with expensive biologics, although the difference was not statistically significant. Overall, psoriasis patients with higher economic status had a lower likelihood of receiving systemic treatments but had a higher probability of being treated with expensive biologics.